The Deity Barbar-babari In Svaneti - Barabadze, Maka (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
The subject matter of the paper is pagan religious relics in Svaneti, in particular worshiping the deity Barbar-babari. Co-habitation of Christianity and paganism used to exist during centuries. People of Svaneti worshiped both the Christian saints and pagan deities, it is visible in pagan habits still prevailing in Christian celebrations. Old traditions are retained in Svaneti, rituals mixed with Christian celebrations, folk sayings are still kept by people, together with archaeological materials they hold great scientific values in terms of exploring the past spiritual practice of our people.